2010
DOI: 10.1063/1.3382912
|View full text |Cite
|
Sign up to set email alerts
|

High-order expansion of T2×t2 Jahn–Teller potential-energy surfaces in tetrahedral molecules

Abstract: Methods from Jahn-Teller theory and invariant theory have been combined for the construction of analytic diabatic potential-energy surfaces of triply degenerate states in tetrahedral molecules. The potentials of a threefold degenerate electronic state of T(2) symmetry, subject to the T(2)xt(2) or T(2)x(t(2)+t(2)) Jahn-Teller effect in a three-dimensional or six-dimensional space of nuclear coordinates, respectively, are considered. The permutation symmetry of four identical nuclei is taken into account in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 36 publications
1
47
0
Order By: Relevance
“…Various theoretical methods and approaches have been used to model properties and reactivities of hydrocarbon radical cations. They range from the early use of qualitative molecular orbital diagrams,42 extended Huckel method,43 and self‐consistent field molecular orbital (SCF‐MO) calculations44,45 to the following methods commonly used nowadays: DFT, Møller–Plesset perturbation theory (MPn), configuration interaction (CI), coupled cluster (CC), complete active space self‐consistent field (CASSCF)/complete active space with a second order perturbation theory (CASPT2),46,47 and CASSCF/multireference configuration interaction (MRCI) 48…”
Section: Theoretical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various theoretical methods and approaches have been used to model properties and reactivities of hydrocarbon radical cations. They range from the early use of qualitative molecular orbital diagrams,42 extended Huckel method,43 and self‐consistent field molecular orbital (SCF‐MO) calculations44,45 to the following methods commonly used nowadays: DFT, Møller–Plesset perturbation theory (MPn), configuration interaction (CI), coupled cluster (CC), complete active space self‐consistent field (CASSCF)/complete active space with a second order perturbation theory (CASPT2),46,47 and CASSCF/multireference configuration interaction (MRCI) 48…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…Methane radical cation demonstrates highly fluxional behavior48,62 as the barrier for interconversion of two degenerate C 2v ‐minima via a C s ‐symmetrical transition structure (TS) is very low [1.1 kcal/mol MP4/6–31G(d,p)//MP2/6–31G(d,p)] 58. The ESR19 and high‐resolution zero‐kinetic‐energy photoelectron (PE) spectroscopy63 of CD 2 H 2 •+ all support a C 2v ‐symmetrical ground state of 1 •+ .…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…[30][31][32][33][34][35][36][37] While the expansions are traditionally 38 truncated at the second order and the resultant Hamiltonians can describe JT and pJT interactions to a qualitative accuracy, a growing number of studies, both theoretical and experimental, have shown inadequacies of the low-order expansions. 17,22,23,[38][39][40][41][42][43][44][45][46][47][48] Motivated by the importance of the high-order expansions, we endeavour to derive general expansion formulas of the JT and pJT Hamiltonian operators up to arbitrary order. [49][50][51][52] In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…However, the diabatic representation within a finite electronic subspace cannot be obtained 18 for a general polyatomic system (N atoms > 2), so one has to resort to approximate diabatiza-tion schemes. [19][20][21][22][23][24][25][26][27] To remain in the unambiguous adiabatic representation, Mead and Truhlar 28 (MT) proposed to compensate for the GP of individual nuclear states by attaching an extra phase factor e iλ (R) , where λ(R) is a function that increases by π on encircling a closed path around the CI seam. This approach was successfully implemented [29][30][31] and applied to many real molecules by Kendrick.…”
Section: Introductionmentioning
confidence: 99%